Contribution to the Analysis of Non-Stationary Random Vibration of Vehicles - Milan Saga (Communications - Scientific letters of the University of Zilina, 2001)
The goal of the paper is to include non-stationary random vibration excitation into the “classic” statistical solution of vehicles. Other vehicle parameters are the deterministic functions. The non-stationary random function will be modelled by changeable speed of the vehicle and vertical unevenness of track. We shall assume evolutionary Gaussian process. The dynamics of railway vehicle motion will be analysed by the Monte Carlo simulation and the theory of Markov processes.